Anal gland adenocarcinoma: a rare case report - Ranganath, Sonika; Bhuta, Prajesh; Chemburkar, Parnasha (International Surgery Journal, 2025)
Anal gland adenocarcinoma is an extremely rare malignancy, with squamous cell carcinoma being the most common type of anal canal cancer. Due to its rarity, there are no well-defined diagnostic criteria or standardized treatment protocols for this condition. This study describes a rare instance of adenocarcinoma in the anal canal, which initially manifested as an anal fistula. The patient received a multifaceted treatment plan encompassing surgical intervention, chemotherapy, and radiotherapy. The study investigates the methods of diagnosis, characteristics of tumours, and the selected treatment approach. This case highlights the challenges in diagnosing and managing anal canal adenocarcinoma. Given its rarity, further studies are needed to establish standardized diagnostic and treatment guidelines.